2015
DOI: 10.3208/jgssp.jpn-20
|View full text |Cite
|
Sign up to set email alerts
|

A study on the bearing capacity of steel pipe piles with tapered tips

Abstract: The problem that occurs during open-ended steel pipe pile installation is that soil enters the pipe and develops frictional resistance that further prevents soil intrusion, causing plugging and increased piling resistance. The steel pipe pile with tapered tip (tapered tip pile) restrains plugging and piling resistance. To apply the tapered tip pile as end-supported piles, it is essential to clarify the bearing capacity mechanism suitable for tapered shapes. In addition, it is not possible to apply the bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Matsumiya et al [10] evaluated the behavior of five piles with varied tapered tip diameters. The piles were evaluated under static compression while being set up in different sand densities, and the results showed that the tapered tip produced less soil plugging and had lower pile resistance than the straight shaft pile.…”
Section: Introductionmentioning
confidence: 99%
“…Matsumiya et al [10] evaluated the behavior of five piles with varied tapered tip diameters. The piles were evaluated under static compression while being set up in different sand densities, and the results showed that the tapered tip produced less soil plugging and had lower pile resistance than the straight shaft pile.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of open-ended steel pipe piles (OESPP), frictional forces are acting on both outer pile shaft surface and inner pile shaft surface. The external frictional resistance on outer pile surface is mobilized between pile surface and the pile's surrounding ground, while the internal frictional resistance on inner pile surface is exerted between pile surface and plugged soils resulted from pile installation process [1]. Examination of these external and internal frictional resistance characteristics is important to evaluate their separate effects on pile ultimate load and behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…The uniform section pile has a mature theory and rich construction experience, while the tapered pile has a high bearing capacity and economic advantage due to the special sloped sidewall. By conducting a model test on the tapered pile, Matsumiya H. et al [20][21] showed that under the same conditions, the bearing capacity per unit volume of the tapered friction pile is 0.5 to 2.5 times higher than that of a common cylinder friction pile, but its engineering cost of foundation treatment is 40% to 60% lower than the latter. By combining the advantages of the rammed cement soil pile and the tapered pile, He J. et al [22][23][24] discussed the bearing capacity advantages of cement soil tapered piles through a model test and proposed a reasonable wedge angle range.…”
Section: State Of the Artmentioning
confidence: 99%
“…After 28 d, the unconfined compressive strength of the rammed cement soil was measured at 0.95 MPa. The deformation modulus of the rammed cement soil was measured at 81.3 MPa by using the test method proposed by Ye S. L. [20].…”
Section: Pile Formation and Test Processmentioning
confidence: 99%